The contribution of expert coaches` experiential knowledge in understanding punching performance in boxers - Lindsay, R. S.; Lenetsky, S. M. (Journal of Emerging Sport Studies, 2020)
Traditionally, the field of sports science has been interested in conducting research that is predominately quantitative in nature. Although this approach has provided significant findings, this has led to expert coaches` experiential knowledge being neglected in favour of empirical knowledge. By investigating punching in boxing, we are interested in developing an understanding of whether elite coaches, through their experiential knowledge, intuitively identify key characteristics of effective punching as identified in controlled experimental research. For this purpose, five interviews were conducted with professional and amateur boxing coaches. From this qualita tive approach it was evident that coaches` knowledge was consistent with that of the empirical research on effective punching performance with four principal components emerging from the interview data. These included: 1) whole body movement, 2) footwork, 3) hip and shoulder rotation, and 4) hand and arm position. The data illuminated how coaches` knowledge can be used to strengthen empirical findings in sports performance, inthis case punching in boxing. Additionally, characteristics of performance that were discussed by coaches that were not identified in the empirical literature highlight directions for further research regarding effective punching technique, an area that requires further investigation before conclusive structures of good practice can be applied.